2004
DOI: 10.1101/gad.1265905
|View full text |Cite
|
Sign up to set email alerts
|

Exonic splicing enhancers in fission yeast: functional conservation demonstrates an early evolutionary origin

Abstract: Discrete sequence elements known as exonic splicing enhancers (ESEs) have been shown to influence both the efficiency of splicing and the profile of mature mRNAs in multicellular eukaryotes. While the existence of ESEs has not been demonstrated previously in unicellular eukaryotes, the factors known to recognize these elements and mediate their communication with the core splicing machinery are conserved and essential in the fission yeast Schizosaccharomyces pombe. Here, we provide evidence that ESE function i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 98 publications
1
29
1
Order By: Relevance
“…Noteworthy here, U2AF 59 is essential for growth [56][57][58]. Moreover, there is some evidence that the recruitment of U2AF 59 to auxiliary factor dependent introns might be mediated by the SR protein Srp2, which has been shown above to be an in vitro substrate of Prp4 kinase [26]. However, we have no data, whether U2AF 59 dependent introns are also Prp4 kinase dependent introns.…”
Section: Inhibition Of Prp4 Kinase Activity Affects Splicing Of Introcontrasting
confidence: 42%
See 1 more Smart Citation
“…Noteworthy here, U2AF 59 is essential for growth [56][57][58]. Moreover, there is some evidence that the recruitment of U2AF 59 to auxiliary factor dependent introns might be mediated by the SR protein Srp2, which has been shown above to be an in vitro substrate of Prp4 kinase [26]. However, we have no data, whether U2AF 59 dependent introns are also Prp4 kinase dependent introns.…”
Section: Inhibition Of Prp4 Kinase Activity Affects Splicing Of Introcontrasting
confidence: 42%
“…Varying the kinase activity with an ATP analog in a fission yeast strain expressing an (analog-sensitive) asPrp4 kinase indicates that recruitment of Srp2 to nascent intron containing transcripts depends on Prp4 kinase activity (D. Eckert and N. F. Käufer, unpublished results). It has been shown that Srp2 promotes the splicing of reporter genes by binding to purine-rich exonic splicing enhancer (ESE) sequences [26]. Based on these observations, we hypothesize that phosphorylation within the SR elements of Srp2 by Prp4 kinase in the nucleus may serve to target Srp2 to ESE containing pre-mRNAs, thereby modulating their splicing efficiency.…”
Section: Function Of Prp4 In Pre-mrna Splicingmentioning
confidence: 99%
“…2F, lanes 4, 6, and 8), whereas the RS domain of Rsd1 alone was sufficient to bind to GST-SpPrp5 (lane 2). Another S. pombe SR protein, SRp2, which is also involved in splicing (40), was tested as a control for RS domain specificity and showed no detectable binding to GSTSpPrp5 (lane 12). Thus, SpPrp5 and Rsd1 interact primarily through their RS/RS-like domains.…”
Section: Identification Of Prp5 Interaction Partnersmentioning
confidence: 99%
“…Importantly, a single bona fide member of the serine/arginine-rich (SR) family of splicing regulators and several SR-like proteins implicated in the regulation of alternative splicing are encoded within the S. pombe genome (22,23). Furthermore, cis-acting sequence elements important in splicing regulation in multicellular eukaryotes have been shown to modulate the splicing efficiency of individual S. pombe introns (24), and indeed nonendogenous plant and mammalian intron sequences have been shown to be properly excised in S. pombe (25,26). Nevertheless, although instances of intron-retention have been documented (27,28), no examples of exon skipping have been described in S. pombe.…”
mentioning
confidence: 99%